2021
DOI: 10.1021/acs.est.1c04596
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Formation and Impacts of Gaseous Nitro-Phenolic Compounds in the Continental Outflow Observed at a Background Site in South China

Abstract: Nitro-phenolic compounds (NPs) have attracted increasing attention because of their health risks and impacts on visibility, climate, and atmospheric chemistry. Despite many measurements of particulate NPs, the knowledge of their gaseous abundances, sources, atmospheric fates, and impacts remains incomplete. Here, 18 gaseous NPs were continuously measured with a time-of-flight chemical ionization mass spectrometer at a background site in South China in autumn and winter. Abundant NPs were observed in the conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 67 publications
(195 reference statements)
3
22
2
Order By: Relevance
“…Furthermore, the good correlations between O 3 and NACs in the daytime (Table S9a in Supporting Information ) confirm the importance of photochemical oxidation for NACs. As reported in previous studies, the photochemical formation of NACs was related to the oxidation of aromatics in the presence of NO 2 (Chen et al., 2021; Finewax et al., 2018; Xu & Wang, 2013; Yuan et al., 2016). Here, the concentration of NACs increased monotonically with the increase of aromatics (Figures S12c and S13c in Supporting Information ) in the daytime, implying the enhanced NACs formati.on with the increase of precursors.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Furthermore, the good correlations between O 3 and NACs in the daytime (Table S9a in Supporting Information ) confirm the importance of photochemical oxidation for NACs. As reported in previous studies, the photochemical formation of NACs was related to the oxidation of aromatics in the presence of NO 2 (Chen et al., 2021; Finewax et al., 2018; Xu & Wang, 2013; Yuan et al., 2016). Here, the concentration of NACs increased monotonically with the increase of aromatics (Figures S12c and S13c in Supporting Information ) in the daytime, implying the enhanced NACs formati.on with the increase of precursors.…”
Section: Resultssupporting
confidence: 61%
“…If the main anthropogenic VOCs (benzene, toluene, phenol, and cresol) are further considered, NO x /VOCs ratios in summer were higher than 4 (nocturnal ratios exceeding 8) (Figure S8f in Supporting Information ). A recent study reported that the NO 3 • oxidation in NO x ‐rich air contributed significantly to the daytime NACs (Chen et al., 2021). Furthermore, the urban Shanghai in summer was under typical high‐NO x conditions (Gao et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direction emissions are mainly from traffic (Kramer et al, 2020;Kurtenbach et al, 2001;Liao et al, 2021), soil (Kubota and Asami, 1985;Oswald et al, 2013;Wu et al, 2019;Xue et al, 2021), biomass burning (Cui et al, 2021;Rondon and Sanhueza, 1989;Theys et al, 2020), and indoor combustion processes (Klosterkother et al, 2021;Liu et al, 2019;Pitts et al, 1985). The reaction of nitric oxide (NO) with OH (Pagsberg et al, 1997;Stuhl and Niki, 1972) is usually thought to be the dominant homogeneous reaction and is significant during daytime, but may be neglected at night due to low OH concentrations, other minor homogeneous HONO sources including nucleation of NO 2 , H 2 O, and NH 3 (Zhang and Tao, 2010), via the photolysis of orthonitrophenols (Bejan et al, 2006;Chen et al, 2021;Lee et al, 2016), via the electronically excited NO 2 and H 2 O (Crowley and Carl, 1997;Dillon and Crowley, 2018;Li et al, 2008) and via HO 2 q H 2 O + NO 2 reaction (Li et al, 2015(Li et al, , 2014Ye et al, 2015). The heterogeneous reactions mainly include nitrogen dioxide (NO 2 ) hydrolysis and reduction reactions on various humid surfaces (Finlayson-Pitts et al, 2003;Ge et al, 2019;Gómez Alvarez et al, 2014;Ma et al, 2013;Marion et al, 2021;Sakamaki et al, 1983;Tang et al, 2017; and nitrate photolysis (Phot nitrate ) (Romer et al, 2018;Ye et al, 2016a, b;Zhou et al, 200...…”
Section: Introductionmentioning
confidence: 99%